The Public Health Innovation Model: Merging Private Sector Processes with Public Health Strengths - Lister, Cameron; Payne, Hannah; Hanson, Carl L.; Barnes, Michael D.; Davis, Siena F.; Manwaring, Todd (Frontiers in Public Health, 2017)
Public health enjoyed a number of successes over the 20th century. However, public health agencies have arguably been ill-equipped to sustain these successes and address the complex threats we face today, including morbidity and mortality associated with persistent chronic diseases and emerging infectious diseases, in the context of flat funding and new and changing health care legislation. Transformational leaders, who are not afraid of taking risks to develop innovative approaches to combat present-day threats, are needed within public health agencies. We propose the Public Health Innovation Model as a tool for public health leaders who wish to integrate innovation into public health practice. This model merges traditional public health program planning models with innovation principles adapted from the private sector, including design thinking, seeking funding from private sector entities, and more strongly emphasizing program outcomes. We also discuss principles that leaders should consider adopting when transitioning to the Public Health Innovation Model, including cross collaboration, community buy-in, human-centered assessment, autonomy and creativity, rapid experimentation and prototyping, and accountability to outcomes.